Second Harmonic Generation Of A Uniaxial Antiferromagnetlc Film. - Lim, Siew Choo (2002)
The second harmonic generation (SHG) of a uniaxial anti ferromagnetic film based. on antiferromagnetic response is calculated and analyzed by using conventional nonlinear, optics approach.